2022
DOI: 10.1002/advs.202200546
|View full text |Cite
|
Sign up to set email alerts
|

Succinylation Inhibits the Enzymatic Hydrolysis of the Extracellular Matrix Protein Fibrillin 1 and Promotes Gastric Cancer Progression

Abstract: Extracellular matrix (ECM) remodeling is crucial in the regulation of gastric cancer (GC) progression. This work aims to reveal novel posttranslational modifications and their relevant mechanisms in GC. In 3D matrix culture and animal models, it is found that fibrillin 1 (FBN1) expression is increased in advanced GC and has succinylation modification. The succinylation modification of FBN1 blocks its degradation by matrix metalloproteinases (MMPs). The long-term accumulation and deposition of FBN1 enhance tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…WSP-5, as an indicator of H 2 S with green fluorescence, was loaded into 4T1 cells to evaluate the intracellular H 2 S level. The addition of 200 μg/mL of BMCPH enhanced the positive fluorescence from 9.99% to 14.3% under flow cytometry (Figure e), and this enhancement could also be clearly observed under fluorescence microscopy (Figure S13), indicating the increased content of H 2 S. Moreover, H 2 S is reported to sulfate a variety of proteins in tumor cells, including MMP-9, an important metalloproteinase that inhibits tumor cell invasion and metastasis; thus a cell scratch experiment was performed on 4T1 cells to further confirm that H 2 S has been effectively produced, in which the cell migration degree in the BMCPH group was lower than that in the control and BMPH groups, proving the effectiveness of releasing H 2 S and then the effective inhibition on tumor cells migration and tumor metastasis rate (Figure S14). Furthermore, the activation of H 2 S on antitumor immune responses was evaluated on mouse lymphoid T cells of CTLL-2.…”
Section: Resultsmentioning
confidence: 79%
“…WSP-5, as an indicator of H 2 S with green fluorescence, was loaded into 4T1 cells to evaluate the intracellular H 2 S level. The addition of 200 μg/mL of BMCPH enhanced the positive fluorescence from 9.99% to 14.3% under flow cytometry (Figure e), and this enhancement could also be clearly observed under fluorescence microscopy (Figure S13), indicating the increased content of H 2 S. Moreover, H 2 S is reported to sulfate a variety of proteins in tumor cells, including MMP-9, an important metalloproteinase that inhibits tumor cell invasion and metastasis; thus a cell scratch experiment was performed on 4T1 cells to further confirm that H 2 S has been effectively produced, in which the cell migration degree in the BMCPH group was lower than that in the control and BMPH groups, proving the effectiveness of releasing H 2 S and then the effective inhibition on tumor cells migration and tumor metastasis rate (Figure S14). Furthermore, the activation of H 2 S on antitumor immune responses was evaluated on mouse lymphoid T cells of CTLL-2.…”
Section: Resultsmentioning
confidence: 79%
“…It can bind to collagen II, IX, and VI through interactions with small leucine‐rich proteoglycans like decorin and/or Biglycan, as well as other ECM components such as cartilage oligomeric matrix protein 23 . Dysregulation of ECM connector molecules has been implicated in carcinogenesis 3,45–48 . Bioinformatics studies have recently identified MATN3 as a prognostic marker for osteosarcoma and gastric cancer 27,30,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer [145], Prostate cancer [146], Colon cancer [147], Renal cell carcinoma [148], Breast cancer [149], Esophageal squamous cell carcinoma [150] Propionylation (Kpr) Propionyl-CoA; propionate 1.Stimulate gene transcription [136] 2. Regulation of protein aggregation in neurodegenerative diseases [151] Glioma [152] Colon cancer [153] Butyrylation (Kbu) Butyryl-CoA; butyrate 1.…”
Section: Acylations Metabolites and Sources Function Types Of Cancer ...mentioning
confidence: 99%